Antibacterial resistance and the success of tailored triple therapy in Helicobacter pylori strains isolated from Slovenian children. Issue 5 (27th June 2017) - Butenko, Tita; Jeverica, Samo; Orel, Rok; Homan, Matjaž
Abstract: Background: Primary Helicobacter pylori ( H. pylori ) infection occurs predominantly in childhood. Antimicrobial resistance is the leading cause for H. pylori eradication failure. The aims of this study were (i) to establish for the first time the antimicrobial resistance of H. pylori strains in infected Slovenian children not previously treated for H. pylori infection and (ii) to evaluate the effectiveness of tailored triple therapy, assuming that eradication rate with tailored triple therapy will be >90%. Methods: Data on all treatment‐naive children 1‐18 years old and treated for H. pylori infection according to susceptibility testing were retrospectively analyzed. All relevant clinical information and demographical information were retrospectively collected from the hospital information systems and/or patients' medical documentation. Results: The inclusion criteria were met by 107 children (64.5% girls) with a median age of 12.0 years (range 2.0‐17.6 years). Primary antimicrobial resistance rates of H. pylori were 1.0% to amoxicillin (AMO), 23.4% to clarithromycin (CLA), 20.2% to metronidazole (MET), 2.8% to levofloxacin (LEV), and 0.0% to tetracycline (TET). Dual resistances were detected to CLA and MET in 11.5% (n=12) of strains, to CLA and LEV in 2.8% (n=3), and to MET and LEV in 2.9% (n=3). Results of treatment success were available for 71 patients (66.2% girls). Eradication of H. pylori was evaluated using the 13C‐urea breath test, monoclonal stool antigen test or in some cases with repeated upper GI endoscopy with histology and cultivation/molecular tests. Eradication was achieved in 61 of 71 (85.9%) patients. Conclusions: The primary resistance rates of H. pylori to CLA and MET in Slovenia are high. Our data strongly support the fact that in countries with high prevalence of resistant H. pylori strains susceptibility testing and tailored therapy is essential.